The Relationship Between the Incidence of Stunting and the Frequency and Duration of Diarrhea in Toddler in the Working Area of Kenjeran Health Center in Surabaya - Arini, Diyah; Faradilah, Ike (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
Infectious diseases (diarrhea) that repeatedly cause childrenÃ¢â‚¬â„¢s health to increase in the pattern of childrenÃ¢â‚¬â„¢s appetite which can lead to less nutritional status of children. This study was to analyze the relationship between the incidence of stunting and the frequency and duration of diarrhea in children underÃ‚Â  five in the Kenjeran Health Center Surabaya Working Area. Analytical research design with cross sectional design in 4 villages in Kenjeran Health Center. Data retrieval is done by questionnaire sheet and observation using microtoise, sample technique uses Sampling Probability by using Stratified Random Sampling as many as 152 children. Data were analyzed using the Spearmen Rho statistical test. The results of research on children under five who experience the incidence of stunting with the frequency and duration of diarrheal disease indicate children who experience stunting and longer frequency. The Rho Spearmen Test showed differences in the incidence of stunting with the frequency of diarrhea p = 0.005 (p<ÃŽÂ± = 0.05), duration of diarrhea p = 0.003 (p<ÃŽÂ± = 0.05). The implication of this study is that stunting is related to the frequency and duration of diarrheal diseases, so that posyandu activities can add counseling about childrenÃ¢â‚¬â„¢s health that requires the treatment of diarrhea in children under five in the Kenjeran Health Center SurabayaÃ‚Â